1999
DOI: 10.1099/13500872-145-6-1409
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the dimethylsulfoxide respiratory (dor) operon of Rhodobacter capsulatus

Abstract: Four genes, dorC, dorD, dorB and dorR of the DMSO respiratory gene cluster of Rhodobacter capsulatus have been identified and sequenced. dorC encodes a pentahaem c-type cytochrome of the NirT class and the derived DorC protein sequence shows highest similarity to TorC from the Escherichia coli trimethylamine-N-oxide (TMAO) respiratory system. Mutagenesis of dorC resulted in the loss of a 46 kDa haem-staining polypeptide from membranes of R. capsulatus. dorD encodes a protein with highest sequence similarity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…Interestingly, disruption of the dorD gene, which encodes a TorD homologue in R. capsulatus, leads to the disappearance of the molybdoenzyme DorA (24). This result points out a relationship between DorD and DorA and suggests that immature DorA is rapidly degraded unless DorD binds to it and allows maturation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, disruption of the dorD gene, which encodes a TorD homologue in R. capsulatus, leads to the disappearance of the molybdoenzyme DorA (24). This result points out a relationship between DorD and DorA and suggests that immature DorA is rapidly degraded unless DorD binds to it and allows maturation.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the absence of TorD in E. coli leads to a significant decrease of the amount of TorA (22). Strikingly, in Rhodobacter capsulatus the absence of DorD results in a complete loss of DorA (24). Finally, in an E. coli MGD-deficient strain, an excess of TorD limits the proteolytic degradation of the TorA cytoplasmic apo form (22).…”
mentioning
confidence: 98%
“…The topology of the trees indicated that dmsB and dmsD are of archaeal evolutionary origin, while for dmsC, no clear correlation with the 16S rRNA phylogenetic tree was observed (data not shown). The small DmsE protein showed some identity (19%) with DorB from Rhodobacter capsulatus, which has been suggested to function in biogenesis of the DMSO reductase in that organism (32).…”
Section: Fig 3 Rt-pcr Analysis Of the Dms Operon Inmentioning
confidence: 99%
“…In Escherichia coli, the molecular components of the DMSO reductase are DmsA, the catalytically active subunit harboring molybdenum-molybdopterin (MPT) as a cofactor; DmsB, a subunit containing iron-sulfur clusters for electron transport; DmsC, a membrane anchor; and DmsD, a molecular chaperone. Other bacterial DMSO and TMAO reductases may contain a membrane-bound c-type cytochrome (DorC or TorC) instead of DmsB and DmsC (17,31,32). The expression of the corresponding dms and tor genes in bacteria may be regulated by a two-component regulatory system (e.g., TorR-TorS) (15,33) or the global oxygen response regulator FNR (6).…”
Section: Comparison Of Dmsrmentioning
confidence: 99%
See 1 more Smart Citation